Brief intensive CBT for pediatric OCD with E-therapy maintenance. (August 2016) - Farrell, Lara J.; Oar, Ella L.; Waters, Allison M.; McConnell, Harry; Tiralongo, Evelin; Garbharran, Vinay; Ollendick, Thomas
Highlights: There were significant reductions on almost all measures following two sessions exposure therapy with e-therapy maintenance. The majority of the sample were reliably improved. At post-treatment, 60% were in remission, and at 6-months follow-up this increased to 70%. Abstract: Cognitive behaviour therapy (CBT), incorporating exposure and response prevention (ERP), has received strong empirical support for the treatment of paediatric OCD, and moreover, is considered the first line treatment of choice (Geller & March, 2012 ). However, despite the availability of effective treatments for this chronic and debilitating disorder, only a small proportion of youth receive these evidence-based approaches. The present study aimed to examine the effectiveness of an intensive ERP-based treatment for youth OCD, using a multiple baseline controlled design. Children and youth ( N = 10; aged 11–16 years) with a primary diagnosis of OCD were randomly assigned to a 1- or 2-week baseline monitoring condition followed by the intervention. The efficacy of the intensive treatment, involving 1 session psychoeducation, 2-sessions ERP plus e-therapy maintenance was examined across parent- child- and clinician-rated measures at post-treatment and 6-month follow-up. Overall, there were significant reductions across time on almost all measures (except self-report anxiety), and moreover, the majority of the sample (80%) were considered reliably improved, and meeting clinically significant change. At post-treatment, 60% were in remission of symptoms, and at 6-month follow-up this increased to 70%. These findings provide strong support for intensive, time-limited approaches to ERP-based CBT for children and youth with OCD.